Considerations for Space Grid Structures: Comprehensive Review of Key Design Aspects and Developing Trends - Hasii, Olena; Gasii, Grygorii; Viktor, Dariienko; Oleksandr, Lizunkov; Ivan, Skrynnik (International Journal of Sustainable Construction Engineering and Technology, 2024)
The investigation aimed to identify key directions for advancing space grid structures. It involved a comprehensive survey of existing structural solutions, nodal connections, and design features specific to spatial rod structures. The analysis included theoretical, numerical, and experimental studies on the stress-strain state, factors influencing it, geometric optimization, and design principles. The focus was on space grid structures, particularly structural plates and their prevalent nodal connections. The investigation revealed that scientific and technological progress, such as improvements in material properties, calculation methods, and software simulations, significantly contributed to the advancement of structural designs by enhancing accuracy and reducing complexity. Geometric dimensions of modular elements and the height-to-span ratio were identified as key parameters affecting structural efficiency. The study also examined global experiences in nodal connection development and provided a general classification of such connections. By identifying advantages and disadvantages of existing space grid structures, potential pathways for further improvement were illuminated. The findings underscored the importance of developing innovative nodal connections as a primary avenue for enhancing space grid structures.